2017
DOI: 10.4103/1119-3077.219518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic dental injuries and associated factors among 8 to 12-years-old schoolchildren in Diyarbakir, Turkey

Abstract: Socio-economic indicators and parents' level of education were not statistically significantly associated with the occurrence of traumatic dental injuries. Factors associated with increased risk of dental injuries in permanent teeth were age, gender, having an incisal overjet greater than 5mm and anterior open bite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 0 publications
4
10
0
23
Order By: Relevance
“…This review identified 3718 articles (Figure ). After screening, full‐text assessment, and contacting 27 authors for further information, a total of 41 studies with 66 366 participants were included in the review (Table ) . Twenty‐seven studies were published within the past 10 years, nine between 10 and 15 years ago, and five were published more than 15 years ago.…”
Section: Resultsmentioning
confidence: 99%
“…This review identified 3718 articles (Figure ). After screening, full‐text assessment, and contacting 27 authors for further information, a total of 41 studies with 66 366 participants were included in the review (Table ) . Twenty‐seven studies were published within the past 10 years, nine between 10 and 15 years ago, and five were published more than 15 years ago.…”
Section: Resultsmentioning
confidence: 99%
“…The confounding variables used in this study were selected on the basis of previous literature. [17][18][19] A P-value lower than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Sex, age, monthly household income, and dental caries experience were used as confounding variables in the adjusted model, independently of the P ‐value in the crude analysis. The confounding variables used in this study were selected on the basis of previous literature . A P ‐value lower than 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Así, la prevalencia de niños con traumatismo dental en esta muestra de pacientes que acudieron a una clínica especializada en odontopediatría en una universidad pública fue del 12%. Esta cifra es similar a la reportada por Freire- (13) Maia et al, (14%) en su estudio realizado en Brasil en niños de 8 a 10 años; más baja que la observada en (14) niños de 3 a 5 años por Sulieman y Awooda (18%) (11) en Sudan, y en Irán por Eslamipour et al, (23.8%) en niños de 9 a 14 años; pero más alta que en el (12) estudio realizado en Turquía por Tumen et al, (4.6%) en niños de 8 a 12 años, y en Reino Unido por (10) Blokland et al, (9%) en sujetos de 8 a 15 años. Sin embargo, es necesario destacar que los intervalos de edad no son exactamente iguales a los incluidos en 6 este estudio.…”
Section: Discussionunclassified
“…Recientes revisiones han explorado la ocurrencia de trauma dental en diferentes regiones del mundo y revelaron que aproximadamente el 30% de los niños en edad preescolar han sufrido un traumatismo dental en la dentición primaria y el 25% de los escolares han sufrido un trauma dental que (9) involucra la dentición permanente . De igual forma, se ha informado una gran variación de su incidencia (10)(11)(12)(13)(14) dentro y entre los países . La variación de la prevalencia del trauma dental entre los estudios puede atribuirse a la ubicación geográfica, las disparidades ambientales y socioeconómicas, los criterios diagnósticos utilizados, así como las (9) diferencias en las muestras estudiadas .…”
Section: Introductionunclassified